Spectrophotometric assessment of tooth bleaching under orthodontic braquets bonded with different materials - CASTRO,Camila Maria Lima de (2017)
Abstract Introduction patients have been submitted to tooth bleaching during orthodontic treatment for aesthetic purposes or to anticipate the replacement of restorations after completion of the treatment. Objective to evaluate the effectiveness of tooth bleaching under orthodontic brackets bonded with different materials. Material and method a hundred bovine enamel blocks were divided into two groups, at-home and in-office tooth bleaching. In-office bleaching was subdivided into five groups (n = 10): HP (control - without brackets); SA(t) - brackets bonded with Transbond XT, without bleaching; SA(fm) - brackets bonded with Orthodontic Fill Magic, without bleaching; HP(t) - brackets bonded with Transbond XT subjected to bleaching; and HP(fm) - brackets bonded with Orthodontic Fill Magic subjected to bleaching. At-home bleaching followed the same treatments, only replacing the bleaching agent. Spectrophotometric assessment was used for tooth color determination at three moments: 1) before staining (baseline); 2) after staining; 3) after bonding the brackets and bleaching procedures. Data were submitted to ANOVA and analyzed by Tukey's test (p < 0.05). Result For both types of bleaching, the control group had an effective bleaching action. Groups using Transbond XT presented greater bleaching potential among the groups with orthodontic accessory, but the bleaching action differed from the positive control. Groups using Orthodontic Fill Magic presented no bleaching action, resembling the negative control groups (artificial saliva). Conclusion the orthodontic bracket impaired the effectiveness of the at-home and in-office bleaching treatment, regardless of the resin used for bonding.